Mathematics learning media development of based computer on translation context in senior high school - Arifa Rahmi; Armiati Armiati; Hendra Syarifuddin (Fakultas Ilmu Pendidikan UNP)
Students faced the difficulty in understanding concept and interpreting of direction of a transformed geometry object, especially translation context. To solved this students difficulty need mathematics learning media which able to clarify translation context and provide them opportunities to learn actively. The aim of this research to know the characteristics and description of mathematics learning media of based computer which is should be valid, practical and effective on translation context in improving the students learning outcomes and their activities. This research wasusingresearch development which apply Plomp model. This model consist of three phase namely initial preliminary research, development or prototyping stage and assessment phase. This research found that mathematics learning media of based computer was valid, practical and effective.